PENGARUH PEMAHAMAN PEMBINAAN KELUARGA KRISTEN TERHADAP KEBAHAGIAAN KELUARGA DI GEREJA BETHEL INDONESIA TABGHA BATAM CENTER - BATAM - George Rudi Hartono Pasaribu; Duma Tambunan; Andreas Eko Nugroho (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
This study aims to determine how much influence Christian Family Development has on family happiness at Bethel Indonesia Tabgha Batam Center Church. By using quantitative methods with a research sample of 120 respondents who have attended Christian pre-marital and post-marital coaching. Data collection techniques by giving questionnaires to respondents, followed by data analysis. The test results show: 1) level (X) is in the high category at significance < 0.05, in the range 218.60 - 223.31 high class, 2) level (Y) is in the high category, at significance < 0.05 , in the range of 115.79 – 119.56, 3) The results of the regression test (X) have a coefficient of 16.389 > 1.987, then Ho is rejected and Ha is accepted. Both variables have a significance value < 0.025 (two sides). Thus, the results of the t test show a positive and significant effect of the variable (X), on (Y), 4) the results of the analysis of determination R Square obtained a number of 0.753 or (75.3%), this indicates that the percentage contribution of the influence of family development (X ) to family happiness (Y) is 75.3%. while the remaining 24.7% is influenced by other variables, it can be concluded that the influence of family development has a high effect on family happiness.